2012
DOI: 10.4317/medoral.17542
|View full text |Cite
|
Sign up to set email alerts
|

Perceived influence of oral health upon quality of life in heart transplant patients

Abstract: Objective: A study was made of heart transplant patient perception of the influence of oral health upon quality of life, based on the Oral Health Impact Profile (OHIP-49) questionnaire validated for Spanish speaking subjects. Design: A cross-sectional evaluation was made of the heart transplant patients followed-up on in the Heart Transplantation Unit of Reina Sofía University Hospital (Spain), using the OHIP-49 questionnaire. The included patients were all over age 18 and signed the corresponding informed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
1
19
0
2
Order By: Relevance
“…This points out to an assumption concluded from studies regarding oral health-related quality of life of organ transplant recipients: an inappropriate estimation of the importance of oral health caused by the general disease burden [32][33][34]. In heart transplanted individuals, the perceived influence of oral health on quality of life was concluded to be reduced [35]. Accordingly, an increased sensibilization and motivation for oral health issues, combined with the information about its importance for patient's general health, seems necessary.…”
Section: Discussionmentioning
confidence: 95%
“…This points out to an assumption concluded from studies regarding oral health-related quality of life of organ transplant recipients: an inappropriate estimation of the importance of oral health caused by the general disease burden [32][33][34]. In heart transplanted individuals, the perceived influence of oral health on quality of life was concluded to be reduced [35]. Accordingly, an increased sensibilization and motivation for oral health issues, combined with the information about its importance for patient's general health, seems necessary.…”
Section: Discussionmentioning
confidence: 95%
“…Oral hygiene in patients with a solid organ transplant has been found to be significantly worse than that of patients on the transplant waiting list. Segura-Saint-Gerons et al [ 11 ] found that Spanish heart transplant recipients had poor self-perceived oral health-related quality of life. However, data on the dental health status of heart transplant recipients (HTRs) are scarce in China.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 summarizes the characteristics of the included examinations. Three studies examined patients after KTx [21,23,27], two examined HTx [22,26] and one study each examined patients after LuTx [24] or LTx [25]. All of the studies were performed in Europe, whereby most investigations took part in Germany.…”
Section: Quality Assessmentmentioning
confidence: 99%